ANALISIS PENGARUH PRODUK DOMESTIK REGIONAL BRUTO (PDRB), INFLASI, DAN INDEKS PEMBANGUNAN MANUSIA (IPM) TERHADAP KETIMPANGAN PENDAPATAN DI DAERAH ISTIMEWA YOGYAKARTA TAHUN 2011-2017 - Dewi Septiani Dwi Kusuma; Sudati Nur Sarfiah; Yustirania Septiani (DINAMIC : Directory Journal of Economic, 2020)
Inequality of income is a problem for all countries, both in developed and developingcountries. The impact of income inequality affects the sustainability of development,especially development in the economic field. D.I Yogyakarta ranks first in the level ofincome inequality in Java during 2011-2017 with the most uneven level of expenditure inJava and outperforming five other provinces. Yogyakarta D.I expenditure levels are unevenbecause residents of D.I Yogyakarta have different consumption patterns. This study aims toanalyze the effect of GRDP, inflation, and HDI on income inequality in D.I Yogyakarta in2011-2017. The type of data in this study uses secondary data from government agenciesinvolved in 2011-2017. The data used in the form of GDP data, inflation, HDI and Gini indexfrom 2011-2017. The analysis model used is panel data regression with the help of theEviews 9. The results of the regression analysis show that partially GRDP, inflation, and HDI have a significant influence on income inequality in D.I Yogyakarta. The results of this study also show that together the GRDP, inflation, and HDI have a significant effect on the income inequality of D.I Yogyakarta.